Relationship Between Red Cell Distribution Width (RDW) and Histopathological Grading and Metastasis in Breast Cancer Patients at Wahidin Sudirohusodo Hospital, Makassar, Indonesia - Makkawaru, Andi Ichsan; Pieter Jr., John; Kusuma, M. Ihwan; Syamsu, Salman Ardi; Smaradhania, Nilam; Sampepajung, Elridho; Faruk, Muhammad (Asian Pacific Journal of Cancer Biology, 2025)
Background: Breast cancer (BC) is a significant global health concern with an increasing incidence. Identifying simple and affordable prognostic indicators for early detection and treatment guidance is crucial. Red Cell Distribution Width (RDW), a hematologic parameter reflecting erythrocyte volume variation, has the potential to indicate systemic inflammation and cancer progression. This study aimed to explore the role of RDW as a prognostic factor in BC patients. Methods: This cross-sectional study involved secondary data from 517 BC patients. The data included age, RDW values, histopathological grade, and metastasis status. Statistical analysis utilized independent T-tests, ANOVA, linear regression, correlation analysis, and Receiver Operating Characteristic (ROC) curves, with a significance level set at ρ<0.05. Results: The mean RDW was 15.4 ± 9.3%. Significant differences in RDW were observed across histopathological grades (Grade 1: 13.29 ± 1.62; Grade 2: 14.53 ± 6.90; Grade 3: 18.28 ± 14.03; ρ<0.001) and between patients with metastasis (16.49 ± 10.0) and without metastasis (15.02 ± 9.01; ρ=0.001). A 1% increase in RDW was associated with a 0.012 increase in histopathological grade (95% CI: 0.006-0.017; ρ=0.001) and a 1.016 times increased odds of metastasis (OR: 1.016; 95% CI: 1.001-1.039; ρ=0.001). The Area Under the Curve (AUC) of the ROC curve for the highest histopathological grade was 0.841 (sensitivity 83.8%, specificity 78.1%), and for metastasis prediction, the AUC was 0.624 (sensitivity 80.6%, specificity 28.7%). Conclusion: RDW demonstrates a significant positive correlation with histopathological grade and metastasis in BC patients, suggesting its potential as an accessible prognostic indicator.